Akuntabilitas Pengelolaan Alokasi Dana Desa (ADD) Di desa luhu kecamatan telaga kabupaten gorontalo - Nurhayati A. Ayuba; Darman Darman; Sudarsono Sudarsono; Djamila Podungge; Ely Ibrahim; Amnatia R Abdullah (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
This study intends to identify the Village Fund Allocation Management in Luhu Village, Telaga District, Gorontalo District. This research was conducted at the Luhu Village Office. The research method used is a descriptive study technique with a qualitative approach in which descriptive research describes the conditions and atmosphere of incidents in the field in a systematic and careful way. The research results prove that the results obtained are tied to the management of village fund allocations in Luhu Village, Telaga District, namely programming Village Fund Allocations, implementation of Village Fund Allocations, and accountability information in accordance with applicable determinations and listed villages that are fast both in administration or stipulations and speed on document collection.